Mooi Indie Image Style in Salon Photography Works - Iljas, Sjuaibun; Regina Octavia Ronald; Akhmad Yani Surachman (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2025)
The application of the Mooi Indie image style in salon photography depicts the natural beauty and traditional life of the archipelago inherited from the colonial era. The image depicts the view of Western nations who consider the Malay region to be exotic and pure as an orientalist discourse. The urgency of this study lies in the need to document and preserve cultural heritage through photography media. The aim is to understand how Mooi Indie elements are applied in contemporary salon photography and have an impact on the appreciation of local culture. The methodology used includes visual analysis of salon photography works. The results of the study show that works with the Mooi Indie image style display a 'beautiful' utopian impression in aesthetic composition, dramatic lighting, and subjects that represent the beauty of nature and tradition. The implication is that the application of this style in salon photography enriches visual aesthetics while contributing to the preservation and promotion of local culture, encouraging public appreciation of Indonesian cultural heritage.